Bacterial contamination of automated MRI contrast injectors in clinical routine - Goebel, Juliane; Steinmann, Joerg; Heintschel von Heinegg, Evelyn; Hestermann, Tobias; Nassenstein, Kai (German Medical Science GMS Publishing House, 2019)
Aim: To quantify the frequency of bacterial contamination of the injected contrast agent/saline solution by an automated contrast injection system, and to evaluate whether usage of a novel tube system can Methods: For bacterial contamination quantification two identical automated piston pump MRI contrast injectors were used in combination with a standard tube system. 3-5 ml of the contrast agent/saline solution was collected from the system prior to its connection to the patients' venous cannula in 104 consecutive patients. To test, whether a novel tube system reduces contamination, a tube system with shielded screw connections was used with the same contrast injectors and contrast agent/saline samples were collected in further 101 patients. Specimens were microbiologically analyzed. Frequencies of contamination were compared using Fisher exact test.Results: With the standard tube system, bacterial contamination was observed in 5.8% (6 out of 104 specimens). With the novel tube system, contamination was observed in 2.0% (2 out of 101 specimens, p=0.280). was the most common germ followed by (2 cases) and (1 case).Conclusion: Bacterial contaminations of MRI contrast injectors occurred in a non-negligible frequency especially with . A trend towards reduced bacterial contamination was seen when a novel tube system with shielded screw connections was used.